Serum 25-hydroxy vitamin D: A possible role in acne vulgaris - Elshahat A Sharaf; Hamdy F Marzouk; Walaa M Abdelmageed; Mohammad A Gaballah (Wolters Kluwer Medknow Publications, 2022)
Background: Acne vulgaris (AV) is a chronic inflammatory disease of the pilosebaceous apparatus. Vitamin D controls the immune system and the proliferation and differentiation of sebocytes and keratinocytes. In addition, it has antioxidant and anti-comedogenic properties. In vitro studies showed that Vitamin D had a functional part in the acne development. Serum Vitamin D levels were previously estimated in AV patients with conflicting results. Objective: To compare 25-hydroxyvitamin D (25[OH] D) serum level in AV patients with healthy controls and to assess the association between 25(OH) D and disease severity to detect any possible role of Vitamin D in AV pathogenesis and treatment. Materials and Methods: 25 (OH) D levels were estimated in 80 AV patients and 40 age- and sex-matched controls using the enzyme-linked immunosorbemt assay technique. Results: 25(OH) D serum levels were significantly lower in patients as compared to controls. Although of no statistical significances, serum 25(OH) D levels were lower in severe and very severe cases than mild and moderate cases. There was significant negative correlation between serum 25(OH) D level and age of onset of AV. However, there were nonsignificant correlations between 25(OH) D blood levels and other patients' characters such as age, sex, occupation, duration of the disease, family history of AV, body mass index, and sites of the lesions. Conclusions: Vitamin D may have a role in the pathogenesis of in AV patients. Further studies on a larger number of patients are recommended to confirm the validity of our results and to evaluate the therapeutic role of Vitamin D supplementation or topical vitamin analogs in acne treatment.